Matematică
victorvornicescu
2015-11-08 22:30:12
( 3 + 6 + 9 + .... + 369 ) - ( 2 + 4 + 6 + .... + 246 ) =?
Răspunsuri la întrebare
elenapoczo
2015-11-09 00:02:06

(3 + 6 + 9 + ... + 369) - (2 + 4 + 6 + ... + 246) = 3(1 + 2 + ... 123) - 2(1 + 2 + 3 + ... + 123) = 1 + 2 + ... + 123 = (123*124)/2 = 123*62 = 7626

dorydory
2015-11-09 00:03:21

Dai factor comun pe 3: Apoi dai factor comun si pe 2: 3•(1+2+3+...+123)-2•(1+2+3+...+123)=3•123•122:2-2•123•122:2=369•61-246•61=22509-15006=7503 Sper ca te-am ajutat!

Adăugați un răspuns